Guias de execução para memorização aplicados à interpretação das Variações Abegg de Robert Schumann - Bragagnolo, Bibiana Maria (2014)
This research tested two different applications of the performance cue s memorization model (CHAFFIN et al., 2002) in Robert Schumann s Abegg Variations. The aim of the first model s application was the memorized public performance of the piece with no memory lapses. The second application, otherwise, adopted a different view of the model and its aim was to improve musical interpretation through the utilization of the performance cues as points of attention during performance, and it purposes were: (1) to test expressive performance cues as points of attention during performance, and its influence in the resulting sound, and (2) to investigate the potentiality of timbre and timing as parameters of the expressive performance cues applied in the Abegg Variations s performances. The methodology was supported by two practice diaries and audio recorded tests of the applications in four public performances. In these performances the number of memory lapses was inexistent or almost inexistent. We also realized a comparative analysis of the timbre and timing in two recordings of these public performances, to verify the result of the use of performance cues projected in the sound. The results of this research confirmed the efficacy of the performance cue s memorization model in the Abegg Variations and also revealed the possibility of using the expressive performance cues in the refinement of the musical interpretation, mainly in the second application of the model.